Wu-Mei-Wan Reduces Insulin Resistance via Inhibition of NLRP3 Inflammasome Activation in HepG2 Cells - Yang, Xueping (Evid Based Complement Alternat Med, 2017)
Wu-Mei-Wan (WMW) is a Chinese herbal formula used to treat type 2 diabetes. In this study, we aimed to explore the effects and mechanisms of WMW on insulin resistance in HepG2 cells. HepG2 cells were pretreated with palmitate (0.25 mM) to impair the insulin signaling pathway. Then, they were treated with different doses of WMW-containing medicated serum and stimulated with 100 nM insulin. Results showed that palmitate could reduce the glucose consumption rate in HepG2 cells and impair insulin signaling related to phosphorylation of insulin receptor (IR) and insulin receptor substrate-1 (IRS-1), thereby regulating the downstream signaling pathways. However, medicated serum of WMW restored impaired insulin signaling, upregulated the expression of phospho-IR (pIR), phosphatidylinositol 3-kinase p85 subunit, phosphoprotein kinase B, and glucose transporter 4, and decreased IRS serine phosphorylation. In addition, it decreased the expression of interleukin-1β and tumor necrosis factor-α, which are the key proinflammatory cytokines involved in insulin resistance; besides, it reduced the expression of NLRP3 inflammasome. These results suggested that WMW could alleviate palmitate-induced insulin resistance in HepG2 cells via inhibition of NLRP3 inflammasome and reduction of proinflammatory cytokine production.